Comparison of the two most commonly used treatments for pyoderma gangrenosum: results of the STOP GAP randomised controlled trial. (12th June 2015) - Ormerod, Anthony D; Thomas, Kim S; Craig, Fiona E; Mitchell, Eleanor; Greenlaw, Nicola; Norrie, John; Mason, James M; Walton, Shernaz; Johnston, Graham A; Williams, Hywel C
Abstract : Objective To determine whether ciclosporin is superior to prednisolone for the treatment of pyoderma gangrenosum, a painful, ulcerating skin disease with a poor evidence base for management. Design Multicentre, parallel group, observer blind, randomised controlled trial. Setting 39 UK hospitals, recruiting from June 2009 to November 2012. Participants 121 patients (73 women, mean age 54 years) with clinician diagnosed pyoderma gangrenosum. Clinical diagnosis was revised in nine participants after randomisation, leaving 112 participants in the analysis set (59 ciclosporin; 53 prednisolone). Intervention Oral prednisolone 0.75 mg/kg/day compared with ciclosporin 4 mg/kg/day, to a maximum dose of 75 and 400 mg/day, respectively. Main outcome measures The primary outcome was speed of healing over six weeks, captured using digital images and assessed by blinded investigators. Secondary outcomes were time to healing, global treatment response, resolution of inflammation, self reported pain, quality of life, number of treatment failures, adverse reactions, and time to recurrence. Outcomes were assessed at baseline and six weeks and when the ulcer had healed (to a maximum of six months). Results Of the 112 participants, 108 had complete primary outcome data at baseline and six weeks (57 ciclosporin; 51 prednisolone). Groups were balanced at baseline. The mean (SD) speed of healing at six weeks was −0.21 (1.00) cm 2 /day in the ciclosporin group compared with −0.14 (0.42) cm 2 /day in the prednisolone group. The adjusted mean difference showed no between group difference (0.003 cm 2 /day, 95% confidence interval −0.20 to 0.21; P=0.97). By six months, ulcers had healed in 28/59 (47%) participants in the ciclosporin group compared with 25/53 (47%) in the prednisolone group. In those with healed ulcers, eight (30%) receiving ciclosporin and seven (28%) receiving prednisolone had a recurrence. Adverse reactions were similar for the two groups (68% ciclosporin and 66% prednisolone), but serious adverse reactions, especially infections, were more common in the prednisolone group. Conclusion Prednisolone and ciclosporin did not differ across a range of objective and patient reported outcomes. Treatment decisions for individual patients may be guided by the different side effect profiles of the two drugs and patient preference. Trial registration Current Controlled Trials ISRCTN35898459 .